Effect of Acellular Bovine Pericardium and Urinary Bladder Submucosa Matrixes in Reconstruction of Ventro-Lateral Hernias in Bucks; Molecular Evaluation: Areeg K. M. Al-ebadi and Ahmed H. F. Al-bayat - Al-ebadi, Areeg K. M. (The Iraqi Journal of Veterinary Medicine, 2019)
The present study aimed to estimate the efficiency of both a cellular bovine pericardium and bovine urinary bladder matrix sheets in the reconstruction of large ventro-lateral hernias in Iraqi bucks by using of molecular evaluation depending on real time-polymerase chain reaction technique to investigate the level of basic-fibroblast growth factor and vascular endothelial growth factor genes during the healing process and reconstruction of the abdominal defects. Under sedation and local anesthesia, (6cm X 8cm size) of ventro-lateral hernias were induced in 24 of Iraqi bucks. The animals were divided randomly into two main equal groups. In bovine pericardium-treatment group, the hernias were treated with onlay implantation of bovine pericardium. While, the hernias in UBM-treatment group were treated with onlay implantation of urinary bladder matrix, 30 days post-inducing of hernias. The molecular evaluation along the period of following-up recorded a significant up-regulation of the level of basic-fibroblast growth factor gene specific for presence of fibroblasts, myofibroblasts and collagen deposition in urinary bladder matrix -treatment group in comparison to bovine pericardium -treatment group with significant difference even at the end of the study. While, a significant up regulation of the levels of angiogenesis classic gene vascular endothelial growth factor were recorded in the bucks of bovine pericardium -treatment group compared to urinary bladder matrix -treatment group. In conclusion; molecular detection of the level of growth factors in target tissue can be used as an important criterion.